2015
DOI: 10.1007/s11356-015-4243-y
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and biochemical response of soil-grown barley (Hordeum vulgare L.) to cerium oxide nanoparticles

Abstract: A soil microcosm study was performed to examine the impacts of cerium oxide nanoparticles (nCeO2) on the physiology, productivity, and macromolecular composition of barley (Hordeum vulgare L.). The plants were cultivated in soil treated with nCeO2 at 0, 125, 250, and 500 mg kg(-1) (control, nCeO2-L, nCeO2-M, and nCeO2-H, respectively). Accumulation of Ce in leaves/grains and its effects on plant stress and nutrient loading were analyzed. The data revealed that nCeO2-H promoted plant development resulting in 33… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
74
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 164 publications
(87 citation statements)
references
References 30 publications
(34 reference statements)
9
74
4
Order By: Relevance
“…In another study, Rico et al (2015) showed that the chlorophyll content in barley leaves was increased at 125-500 mg/kg nano-CeO 2 , similar to our observations in LOMS leaves. The slight increase in the chlorophyll a (Fig.…”
Section: Impact Of Nano-ceo 2 On Plant Growthsupporting
confidence: 90%
“…In another study, Rico et al (2015) showed that the chlorophyll content in barley leaves was increased at 125-500 mg/kg nano-CeO 2 , similar to our observations in LOMS leaves. The slight increase in the chlorophyll a (Fig.…”
Section: Impact Of Nano-ceo 2 On Plant Growthsupporting
confidence: 90%
“…The accumulation of nanomaterials in plants has been shown to increase the shoot length, chlorophyll b content, number of adventitious roots, and fresh root weight of rice seedlings [13]. A 500 mg/kg CeO 2 treatment was shown to increase the plant height, chlorophyll content, and biomass of barley without any toxic effects [14]. GO treatments decreased the damage caused by Cu stress by neutralizing the effects of Cu on nutrient accumulation in Lemna minor [3], and TiO 2 nanoparticles have been reported to improve phosphorus uptake and improving plant growth [15].…”
Section: Plant Responses To Nanomaterials Depends On Multiple Factorsmentioning
confidence: 99%
“…The overall process will eventually trigger oxidative damage and ultimately cell death (Sharma et al, 2012). There are several works reporting that ENMs have a tendency to induce ROS generation Navarro et al, 2008;Lee et al, 2010;Rico et al, 2015aRico et al, , 2015b. Other reports show results pertaining to genetic, hormonal, and other biomolecule disruptions (Atha et al, 2012;Zhao and Liu, 2012).…”
Section: Reactive Oxygen Species (Ros) Production and Other Biochemicmentioning
confidence: 99%